Bringing the patient voice into the operating room: engaging patients in surgical safety research with the Operating Room Black Box® - Etherington, Cole; Lê, Maxime; Proulx, Laurie; Boet, Sylvain (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Surgery is one of the most common patient experiences in the health care system. Yet, efforts to engage patients in surgical safety research have not matched those of other health care fields. This is a critical issue given the nature of surgery inhibits patients’ abilities to advocate for themselves as they are typically under anesthetic when the procedure is performed. We partnered with patients throughout our research program, which uses the Operating Room Black Box® to enhance surgical patient safety through transparent and proactive analysis of human factors to detect and prevent avoidable errors. Main body In this article, we outline the need for, and our approach to, patient engagement in surgical safety research. Our approach included a series of planned activities and skill development opportunities designed to build capacity and bring together patients, clinicians, and researchers to inform research and practice. We also conducted evaluation surveys during the first year of our program, which have indicated a positive experience by both patient partners and the research team. Conclusion We believe our approach can serve as an important first step toward building a model for patient engagement in the surgical safety field and could significantly contribute to improved quality of care and outcomes for surgical patients.

Plain English summary Although surgery is one of the most common patient experiences, patients have not been engaged in surgical safety research. Patients were engaged as patient advisors in the use of the Operating Room Black Box® at The Ottawa Hospital. The Operating Room Black Box® is a tool that is used in the operating room (OR) which captures audio, video, patient vital signs and other information that are analyzed for research purposes. The aim of the OR Black Box® is to learn from experience and improve practice and care. Patient advisors influenced the nature of the activities undertaken, co-developed the communication materials for patients, evaluated patient engagement practices, and disseminated the research results. These patient engagement activities are an important first step in engaging patients in surgical safety research.